2020
DOI: 10.5089/9781513550268.001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Containment Measures on the COVID-19 Pandemic

Abstract: Countries have implemented several containment measures to halt the spread of the 2019 coronavirus disease, but it remains unclear the extent to which these unprecedented measures have been successful. We examine this question using daily data on the number of coronavirus disease cases as well as on real-time containment measures implemented by countries. Results suggest that these measures have been very effective in flattening the “pandemic curve”, but there is significant heterogeneity across countries. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 5 publications
13
129
0
1
Order By: Relevance
“…Our finding of inverse correlation between cCHI values and cumulative incidences of COVID-19 is strengthened by controlling for population density. This is in line with previously reported finding that higher population density renders social distancing more difficult and that the effect of containment measures have been stronger in countries with lower population densities 25 . Further, our finding of statistically significant and positive correlation between population density and cumulative incidence of COVID-19 across 28 European countries agrees with previous report on greater rates of transmission of SARS-CoV-2 in the U.S. counties with greater population densities 29 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of inverse correlation between cCHI values and cumulative incidences of COVID-19 is strengthened by controlling for population density. This is in line with previously reported finding that higher population density renders social distancing more difficult and that the effect of containment measures have been stronger in countries with lower population densities 25 . Further, our finding of statistically significant and positive correlation between population density and cumulative incidence of COVID-19 across 28 European countries agrees with previous report on greater rates of transmission of SARS-CoV-2 in the U.S. counties with greater population densities 29 .…”
Section: Discussionsupporting
confidence: 93%
“…Early adoption and stringent containment measures were previously found to be associated with lower number of cases and deaths due to COVID-19. For instance, implementation of restrictions on gatherings and public events in New Zealand when number of daily cases was in single digits reduced the number of COVID-19 deaths by at least ten times relative to the number of deaths expected in the absence of stringent containment measures 25 . Likewise, cities in China that pre-emptively suspended intra-city public transport and banned public gatherings and entertainment venues had in average 33.3% fewer cases during the first weeks of their outbreaks, compared with cities that started control later 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study relates closely to a rapidly growing literature on the dynamics of stock prices, economic activity, and policy actions during the coronavirus pandemic. Notable contributions include Alan et al 2020, Caballero and Simsek (2020), Chen and Spence (2020), Cox et al (2020), Deb et al (2020), Giglio et al (2020), Gormsen and Koijen (2020), and Landier and Thesmar (2020). 4 Relative to these papers, we contribute by documenting the predictive content of national stock prices for near-future economic activity and by providing evidence that stock prices fall sharply with the stringency of lockdown measures, conditional on a battery of controls for pandemic severity, mobility, and the generosity of income support and debt relief policies.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that containment measures being implemented in different countries are very effective in flattening the pandemic curve. Further, it was highlighted that effectiveness was enhanced when the containment measures were implemented quickly [10].…”
Section: Rationalementioning
confidence: 99%